Information and Communication Technologies in the Translation Process - Seljan, Sanja (Array, 2011)
Development of contemporary society characterized by the globalization on one side, and the necessity for preservation of cultural identity on the other side, has caused indispensable use of information and communication technologies in everyday work. Quick access to information, common market, intercultural communication and cooperation activities are deeply influenced by the growing need to overcome language barriers. The growing demand for the translation work in national and multinational institutions, cooperation activities, as well as principles of multilingualism and open access to documents in the proper language, have imposed considerable changes on the translation process. The present situation gives rise to numerous issues: translators’ education, changes in professional and organizational workflow, building of adequate translation tools and resources according to the standards, cooperation between industry and university, integration of Croatian modules into existing systems, team work and data-sharing, government support and financing, international cooperation, national priorities and strategy development. Translators’ education, compatible with the existing European model, should integrate theory and practical work: language knowledge and skills, use of information and communication technology, supplemented by cultural background, ethical awareness and presentation skills. Building of Croatian translation resources and use of information and communication technology, especially computer-assisted translation tools, would enable answering the needs of multilingual communication, integration into the European environment and language preservation.